Do Remittances Have a Flip Side? A General Equilibrium Analysis of Remittances, Labor Supply Responses and Policy Options for Jamaica - Bussolo, Maurizio; Medvedev, Denis (2012)
Econometric analysis established a negative relationship between labor supply and remittances in Jamaica. We incorporate this ex-post evidence in a general equilibrium model to investigate economy-wide effects of increased remittance inflows. In this model, remittances reduce labor force participation by increasing reservation wages of recipients. This exacerbates the real exchange rate appreciation, hurting Jamaica's export base and small manufacturing import-competing sector. Within the narrow margins of maneuver of a highly indebted government, we show that a revenue-neutral policy response of a simultaneous reduction in payroll taxes and increase in sales taxes can effectively counteract these potentially worrisome effects of remittances.